Splenectomy in large splenomegalies - Guzmán, Prudencio; Borges, Freddy; Priario, Julio C (Cirugía del Uruguay, 1974)
The paper contains a rev1s1on of 19 case histories of patients who underwent splenectomy due to splenomegaly, considering as such all spleens with a weight above 260 grs. Age, sex, weight of spleen and surgical technique were considered. Prior ligature of splenic artery is deemed important since it prevents serious hemorrhage and favours "self-transfusion". In view of the· fact that the first surgical act should consist of ligature of pedicle, the abdominal approach is advisable.